Polarized training is not optimal for endurance athletes: Response to Foster and colleagues - Burnley, M.; Bearden, S. E.; Jones, A. M. (Medicine & Science in Sports & Exercise, 2022)
There is no question that endur ance athletes should, and typically do, complete an appropriate volume of training commensurate with the demands of the event being trained for and their physiological status. Moreover, the need to balance the demands of longer, lower-intensity train ing sessions against shorter, higher-intensity training sessions to simultaneously optimize physiological adaptation and min imize the risk of overtraining is noncontentious. This balance is often managed by alternating harder and easier training days and by changes in emphasis between training microcycles and mesocycles. It is also apparent that type I and type II muscle fibers may be recruited and therefore "trained" using a wide variety of training sessions (16,17), and it seems likely that a range of training programs could result in a similar overall out come. The purpose of this exchange of "contrasting perspec tives" was not to debate these old and rather obvious points but for us to challenge and for Foster et al. to defend the notion that genuine polarized training, which is presently in vogue, is superior to other training models. Foster et al. criticized thresh old (zone 2-dominant) training, but then combined polarized with pyramidal training in the remainder of their argument. Thus, Foster et al. used the very training intensity they rejected as the means to support their position. We conclude that there is presently no evidence that a specifically polarized training intensity distribution is optimal. Balanced and effective training programs for endurance athletes do and should prioritize zone 1 and zone 2 over zone 3: that is, pyramidal (nonpolarized) train ing. We rest our uncontested case.